Integração bicicleta - transporte público: Barreiras e oportunidades para a acessibilidade da população de baixa renda em Fortaleza - Costa, Taís Barreto (2019)
Most of the studies that discuss the integrated use of bicycle to public transport as a mode of access/diffusion focus on the reality of developed countries. Few bring the context of developing countries where predominate conditions of socioeconomic inequality and low accessibility to opportunities by less favored groups. There is evidence in the literature that the mode of access/egress to public transport can be an important tool to improve the accessibility to the opportunities in the cities, therefore making relevant the study of the phenomenon in these realities. In the city of Fortaleza, a large part of the low-income population lives in conditions of socio-spatial segregation and experiences low levels of accessibility to opportunities in the city. However, recent investments in public transport and cycling have been carried out in recent years and the integration between bicycle and buses has been stimulated. The purpose of this study is, therefore, to better understand the phenomenon of bicycle - public transport integration in the context of large cities in developing countries, assessing the barriers and opportunities of this alternative of travel to reduce the problems of accessibility of the low - income population in a case study of Fortaleza. The study is conducted through quantitative-qualitative research. For the analysis were used surveys performed by the City of Fortaleza and operational data of the public transportation and bicycle systems seeking to advance in the discussions about the phenomenon and its complexity in the context of Fortaleza.